Effects of a Self-Efficacy Enhancing Program on Exercise Behavior, Blood Pressure Level and Body Mass Index among a Pre-hypertension Group with Overweight, Sukhothai Province - Panboot, Nuttapong; Danyuthasilpe, Chuleekorn; Na-udom, Anamai (NU Journal of Nursing and Health Sciences, 2023)
The purpose of this quasi-experimental research aimed to examine the effects of a self-efficacy enhancing program on exercise behavior, blood pressure level and body mass index among a risk group of overweight participants. A cohort of 60 participants used a simple random sampling method was divided into two groups of 30 each, designated as the control group or the experimental group. The experimental group undertook a self-efficacy-enhancing program while the control group received regular nursing care. The self-efficacy program was based on Bandura's self-efficacytheory. The content validity index of the exercise behavior questionnaires was 0.95 with a reliability of 0.76 and the content validity index of the Self-efficacy questionnaires was 0.90 with a reliability of 0.74. The data were analyzed by descriptive statistics and a t-test. The outcomes of the programs were: 1) After program implementation, the average score for exercise behavior of the experimental group was statistically significantly higher than before program implementation while the blood pressure level and body mass index of the experimental group was statistically significantly lower than before program implementation (p < 0.05) 2) After program implementation, the average score of exercise behavior of the experimental group were statistically significant higher than the control group's average score of exercise behavior while the blood pressure level and body mass index of the experimental group were statistically significantly lower than that of the control group. (p <0.05) These results suggest that community nurse practitioners can valuably apply the self-efficacy enhancing program based on Bandura's self-efficacy theory to increase awareness of, and promote exercise behavior as a means to prevent hypertension.